Decentralized motion control of multiple holonomic agents under input constraints - Dimarogonas, Dimos V.; Zavlanos, Michael M.; Loizou, Savvas (My University, 2003)
The navigation function methodology, established in previous work for centralized multiple robot navigation, is extended for decentralized navigation with input constraints. In contrast to the centralized case, each agent plans its actions without knowing the destinations of the other agents. Asymptotic stability is guaranteed by the existence of a global Lyapunov function for the whole system, which is actually the sum of the separate navigation functions. The collision avoidance and global convergence properties as well as input requirements are verified through simulations.
Keywords: Computer simulation; Mobile robots; Navigation